Elevating Tanzania’s Tourism: Integrating GIS, AR and AI for Immersive Exploration and Promotion - Kumbo, lazaro Inon; Juma, Shabani Bakari; Mushi, Martin Ludovick (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This study presents a comprehensive examination of the integration of Geographic Information Systems (GIS), Augmented Reality (AR) and Artificial Intelligence (AI) in tourism promotion in Tanzania. The literature review underscores the significance of these technologies in enhancing visitor experiences, destination management, and marketing strategies. The proposed integrated system design combines GIS’s spatial mapping capabilities, AI’s personalised recommendations, and AR’s immersive content delivery to optimise tourist satisfaction and engagement. Key components include the GIS module for spatial data management, the AI recommendation engine for personalised suggestions, and the AR interface for immersive content overlay. Discussions highlight how the proposed system, by addressing critical challenges in the tourism sector, aligns with existing research findings and reassures its effectiveness. Ultimately, the study emphasises the potential of GIS, AR and AI technologies to revolutionise tourism promotion in Tanzania, fostering sustainable growth and cultural appreciation while enhancing visitor experiences.